Variation of comsitional content in subsurface layers of Hastelloy type alloys as caused by melt of fluorides ZrF₄– NaF and electron irradiation - Azhazha, V.М.; Bakai, A.S.; Bobrov, Yu.P.; Dovbnya, A.N.; Lavrinenko, S.D.; Pylypenko, M.M. (Вопросы атомной науки и техники, 2005)
The secondary-ion mass-spectrometry technique was employed to study the compositional content variation in subsurface layers of alloys of Hastelloy type that had been irradiated with electron beam with the average energy 9.6 MeV in the melt of sodium and zirconium fluoride salts at the temperature 650°С for 700 hours.